PENGGUNAAN MEDIA GOOGLE SITE DALAM PEMBELAJARAN UNTUK MENINGKATKAN EFEKTIFITAS BELAJAR PESERTA DIDIK SEKOLAH DASAR - Yushtika Muliana Pubian; Herpratiwi Herpratiwi (Akademika, 2022)
Conventional learning methods are currently felt to be no longer in accordance with the changes in the industrial revolution era, the learning method is actually a way of delivering educators to students in the learning process in the classroom, Learning through applications is an educational innovation to answer the challenge of the availability of varied learning resources. One of the right types of media in the process of making teaching materials is the Google Site Application. The purpose of this study was to determine the development of Google Site media in learning to increase the learning effectiveness of elementary school students. The method used in this study uses the SLR (Systematic Literature Review) method. Data collection is carried out using documentation and reviewing all articles related to the Google Site. Based on the results of the research that has been carried out in the research results table, it explains that the google site can be used as a medium or learning method in the classroom, especially in the 21st century and the technological industrial revolution. elementary school level